What caused severe air pollution episode of November 2016 in New Delhi?. (1st February 2020) - Kanawade, V.P.; Srivastava, A.K.; Ram, K.; Asmi, E.; Vakkari, V.; Soni, V.K.; Varaprasad, V.; Sarangi, C.
Abstract: In recent years, South Asia is experiencing severely degraded air quality, with particulate matter less than 2.5 μm (PM2.5 ) reaching unprecedented high levels. Here, we investigate a severe air pollution episode (SAPE) witnessed in New Delhi during 1–7 November 2016. This was a very unusual air pollution episode wherein air quality index exceeded >500 and was persistent for about a week encapsulating the entire Indo-Gangetic Plain (IGP). We demonstrate that a stagnant weather condition was the dominant cause of the SAPE. Mean concentration of PM2.5 in New Delhi before, during, and after the SAPE were 142 μg/m 3, 563 μg/m 3, and 240 μg/m 3, respectively. Satellite-based aerosol optical depth (AOD), ultraviolet-aerosol index (UV-AI) and surface carbon monoxide (CO) concentrations also showed significant enhancements over large locale spatially by about 50–70% during the SAPE. A large and simultaneous increase in UV-AI and CO downwind of a large number of fire hotspots (Punjab and Haryana) is a clear indication of biomass burning aerosols. Analysis of absorption Ångström exponent further substantiates this finding, showing a large fraction of light absorbing carbonaceous-type aerosols. Radiosonde observations clearly showed that stagnant atmospheric conditions led to SAPE in New Delhi by allowing pollution to accumulate and persist in the near-surface environment. As a result new particle formation was suppressed due to very high pre-existing aerosol concentrations during the SAPE. The heating rate induced by light absorbing aerosols into an atmospheric layer during SAPE was also very high (3.1 ± 0.7 K/day). These findings will help in understanding air quality and climate effects, as well as in formulating policies to mitigate these complex pollution episodes in an anthropogenic future. Highlights: Satellite products offer entrenched approach to monitor near-surface air quality. New Delhi witnessed the worst severe air pollution episode during November 2016. Air stagnation played a vital role in the occurrence of severe air pollution episode.